2011
DOI: 10.3133/sir20115064
|View full text |Cite
|
Sign up to set email alerts
|

Sediment concentrations, loads, and particle-size distributions in the Red River of the North and selected tributaries near Fargo, North Dakota, during the 2010 spring high-flow event

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Goharrokhi and Clark (2015) found that sediment distribution over the depth and cross section of the Red River in Winnipeg was relatively uniform. Blanchard et al (2011) found that 99% of the total sediment load through the Red River approximately 300 km upstream of the present study reach was suspended load, and that the bed load contribution in total sediment in the Red River was negligible. Goharrokhi and Clark (2015) confirmed that these results were true for the Red River within the city of Winnipeg as well.…”
Section: Case Study: Red River In Winnipeg Canadamentioning
confidence: 45%
“…Goharrokhi and Clark (2015) found that sediment distribution over the depth and cross section of the Red River in Winnipeg was relatively uniform. Blanchard et al (2011) found that 99% of the total sediment load through the Red River approximately 300 km upstream of the present study reach was suspended load, and that the bed load contribution in total sediment in the Red River was negligible. Goharrokhi and Clark (2015) confirmed that these results were true for the Red River within the city of Winnipeg as well.…”
Section: Case Study: Red River In Winnipeg Canadamentioning
confidence: 45%
“…Runoff velocity (m s −1 ) was measured using the Valeport ‘Braystoke’ Model 001 current meter. The velocity/area method (FAO, ) was used to estimate total runoff discharge (Equation 4), while sediment discharge was calculated from suspended sediment concentration samples (Blanchard et al, ) (Equation 5), Q0.25em=0.25emA0.25emx0.25emV Qs=0.25emQ0.25em*0.25emCs*0.25emK …”
Section: Methodsmentioning
confidence: 99%
“…The average contributions of < 2 µm and 2-63 µm fractions in suspended sediment of the Yangtze River were 48.1% and 51.9%, respectively (Yu et al, 2011). For the Red River, the Maple River, the Sheyenne River, and the Wild Rice River, 75-99% of the suspended sediment was below 62 µm (Blanchard et al, 2011). Walling et al (2000) reported that >95% of the suspended sediment was below 63 µm for the Humber River and the Tweed River (UK).…”
Section: Suspended Sediment Particle Size During Water and Sediment Rmentioning
confidence: 99%